The Effect of Push Up Training Using Resistance Band Weights on Increasing The Arm Muscle Power of Basketball Players - Maria Amanda Helena Sitinjak; Berliana; Ridha Mustaqim; Mulyana (Universitas Negeri Semarang, 2025)
Arm muscle power is very important to support various aspects of the game in sports matches, especially in basketball. Arm muscle power supports motion when shooting, dribbling, passing, defense or offense. This study aims to determine the effect of push up training using resistance band weights and on increasing the arm muscle power of basketball players. The method used in this research is a quantitative experimental method with a pretest-posttest control group design. The population in this study were women’s basketball players of Club Bandung Utama with an age group of 14 as many as 27 people. The sampling technique in this study used a total sampling technique with the total population (27 people) used as research samples. The test instrument in this study used a medicine ball test to measure arm muscle power. The results of this study indicate that push up training using resistance band weights provides a significant increase in the arm muscle power of basketball players besides that push up training using resistance band weights has a significant effect compared to push ups without using resistance band weights. This shows that push ups using resistance band weights contribute to increasing the arm muscle power of basketball players where arm muscle power is an important component in the game of basketball, because good arm muscle power can support basic technical movements and complex techniques even in the sport of basketball.This study provides recommendations for coaches to be able to use training methods using resistance bands to increase the arm muscle power of basketball players.